Deep-sea corals from the seamounts of Central and Southwest Indian Ridges - Periasamy, Rengaiyan; Kurian, Palayil John; Ingole, Baban (Zootaxa, 2025)
Deep-sea coral biodiversity and abundance have been used to indicate the overall health of the deep-sea benthic ecosystem and its capacity for supporting life. The growing interest in the mineral-rich environments of the Indian Ocean Ridge system brings the necessity of a more complete understanding of the deep-sea benthic ecosystems. Baseline studies conducted in potential mineral exploration areas have identified seven deep-sea coral species in the Central Indian Ridge (CIR) and the Southwest Indian Ridge (SWIR). In the present study, these species, including one Crypthelia, were identified, with the other six representing significant range extensions. The hydrozoan Pseudocrypthelia apoma Cairns, 2015, is recorded for the first time in the Indian Ocean, and five anthozoans are reported as new records for this region. Among these, three belong to the class Hexacorallia: Caryophyllia ephyala (Alcock, 1891), Trochocyathus patelliformis (Cairns, 1999), and Deltocyathus cameratus (Cairns, 1999). The other two species are the Octocorallia Callozostron mirabile (Wright, 1885) and Faxiella delicatula (Thomson & Rennett 1931). These species were sampled on seamounts formed by ultramafic mantle and basalts near polymetallic sulfide areas of CIR and SWIR. These findings contribute to the knowledge of deep-sea coral diversity from the CIR and abyssal SWIR.